Strong social disparities in access to IVF/ICSI despite free cost of treatment: a French population-based nationwide cohort study - Khaoula Ben Messaoud; Juliette Guibert; Jean Bouyer; Elise de La Rochebrochard (BMC, 2023)
Abstract Background Access to IVF/ICSI is facilitated when the financial barrier is removed. In a national context where in vitro fertilisation (IVF)/intracytoplasmic sperm Injection (ICSI) treatment is cost-free, how many women do not access IVF/ICSI and what are the factors associated with non-access? Methods Using French national health insurance databases, the cohort included 20,240 women aged 18-43 years living in France who underwent unsuccessful treatment (no pregnancy) with clomiphene citrate (CC) and/or gonadotropins with treatment started between January and August 2016. The outcome measure was non-access to IVF/ICSI during the 24-month following start of infertility care. Factors associated with non-access to IVF/ICSI were explored using mixed effects logistic regression. Results In the cohort, 65.4% of women did not access IVF/ICSI. In multivariable analysis, non-access to IVF/ICSI was higher in younger women (18-25 years: (OR 2.17, 95% CI: 1.85-2.54) and in older women (40-43 years: (OR=3.60, 95% CI: 3.25-3.98)). Non-access was higher among women below the poverty line (OR=3.76, 95% CI: 3.34-4.23) and showed a significant upward trend with increasing deprivation of place of residence. Distance to the nearest fertility centre was not significantly associated with non-access to IVF/ICSI. Conclusions In a national context of cost-free ART treatment, a large proportion of women did not access treatment, with a strong social gradient that raises important issues. We need to understand the underlying social mechanisms to develop an efficient and equitable health policy regarding infertility care.